Metabolic syndrome and drug discontinuation in schizophrenia: a randomized trial comparing aripiprazole olanzapine and haloperidol. (7th August 2015) - Parabiaghi, A.; Tettamanti, M.; D'Avanzo, B.; Barbato, A.; ,
Abstract : Objective: To determine whether the prescription of aripiprazole, compared with olanzapine and haloperidol, was associated with a lower frequency of metabolic syndrome (MS) and treatment discontinuation at 1 year. Method: Patients were randomly assigned to be treated open‐label and according to usual clinical practice with either aripiprazole, olanzapine, or haloperidol and followed up for 1 year. Results: Three hundred out‐patients with persistent schizophrenia were recruited in 35 mental health services. The intention‐to‐treat (ITT) analysis found no significant differences in the rate of MS between aripiprazole (37%), olanzapine (47%), and haloperidol (42%). Treatment discontinuation for any cause was higher for aripiprazole (52%) than for olanzapine (33%; OR, 0.41; P = 0.004), or haloperidol (37%; OR, 0.51; P = 0.030). No significant difference was found between olanzapine and haloperidol. Time to discontinuation for any cause was longer for olanzapine than for aripiprazole (HR, 0.55; P < 0.001). No significant differences were found between haloperidol and aripiprazole, or between olanzapine and haloperidol. Conclusion: The prescription of aripiprazole did not significantly reduce the rates of MS, but its treatment retention was worse. Aripiprazole cannot be considered the safest and most effective drug for maintenance treatment of schizophrenia in routine care, although it may have a place in antipsychotic therapy.